2001
DOI: 10.1677/joe.0.1710273
|View full text |Cite
|
Sign up to set email alerts
|

IGFBPs modulate IGF-I- and high glucose-controlled growth of human retinal endothelial cells

Abstract: Insulin-like growth factor binding proteins (IGFBPs) are important local factors in the development of proliferative diabetic retinopathy. We investigated the effects of IGF-I and increased glucose concentrations on the release of IGFBPs and the growth of human retinal endothelial cells (HRECs). HRECs secrete IGFBPs-2 to -5. IGF-I stimulated thymidine incorporation and modified the pattern of IGFBPs, decreasing the inhibitory IGFBP-4 through down-regulation of its mRNA, and increasing IGFBP-5 which, per se, wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 41 publications
2
16
0
Order By: Relevance
“…A difference in binding characteristics depending on the incorporated IR halfdimer, IRA or IRB, has been reported (Pandini et al, 2002), but recent studies suggest that both types of hybrid receptors have the same affinity for IGF-I and insulin (Benyoucef et al, 2007, Slaaby et al, 2006. The lack of insulin effect on DNA-synthesis in HMVEC is in agreement with our previous observation (Chisalita and Arnqvist, 2004) together with several other reports on microvascular cells (Artwohl et al, 2007, Giannini et al, 2001 suggesting that human microvascular endothelial cells are insulin resistant. Because of the cross-reactivity of insulin and IGF-I at high concentrations it is very important to use physiological or near physiological concentrations of the peptides when studying insulin and IGF-I effects in vitro on cells that express both IR types and IGF-IR, and also to make sure of which receptor is activated.…”
Section: Mce-d-08-00188 Revised Manuscriptsupporting
confidence: 88%
See 1 more Smart Citation
“…A difference in binding characteristics depending on the incorporated IR halfdimer, IRA or IRB, has been reported (Pandini et al, 2002), but recent studies suggest that both types of hybrid receptors have the same affinity for IGF-I and insulin (Benyoucef et al, 2007, Slaaby et al, 2006. The lack of insulin effect on DNA-synthesis in HMVEC is in agreement with our previous observation (Chisalita and Arnqvist, 2004) together with several other reports on microvascular cells (Artwohl et al, 2007, Giannini et al, 2001 suggesting that human microvascular endothelial cells are insulin resistant. Because of the cross-reactivity of insulin and IGF-I at high concentrations it is very important to use physiological or near physiological concentrations of the peptides when studying insulin and IGF-I effects in vitro on cells that express both IR types and IGF-IR, and also to make sure of which receptor is activated.…”
Section: Mce-d-08-00188 Revised Manuscriptsupporting
confidence: 88%
“…Other studies on microvascular endothelial cells suggest that HMVEC as well as glomerular (Giannini et al, 1999) and retinal microvascular endothelial cells (Giannini et al, 2001) are very sensitive to IGF-I indicating a physiological function of IGF-I.…”
Section: Mce-d-08-00188 Revised Manuscriptmentioning
confidence: 93%
“…Another study demonstrated that human retinal endothelial cells secrete IGFBP2, IGFBP3, IGFBP4 and IGFBP5 (Giannini et al 2001). GH, VEGF, FGF2 and PDGF had no effect on IGFBP levels, whereas IGF1 decreased IGFBP4 and increased IGFBP5 levels.…”
Section: Diabetic Retinopathymentioning
confidence: 99%
“…There is a lack of studies regarding effects of insulin and IGF-I on glucose metabolism and DNA synthesis in human endothelial cells. An effect of IGF-I on [ 3 H]thymidine incorporation into DNA has been reported in human retinal endothelial cells (14). The aim of our study was to characterize IR and IGF-IR in human micro-and macrovascular endothelial cells with regard to gene expression, ligand binding, receptor activation, and the biological effect of insulin, glargine, and IGF-I.…”
mentioning
confidence: 96%